An Analysis of Mutual Cooperation Values in the ELT Textbook for the Eighth Grade Students of Junior High School - Nur Lailatul Hidayah (Faculty of Education, 2025)
In education, the value of mutual cooperation is one part of the Pancasila Students’ Profile which is considered important in developing student character. One of the main reasons is that this value has begun to fade along with the times due to social inequality, lack of tolerance, and concern for others which can lead to indifference, selfishness, low sympathy, and empathy for others (Andika, 2022). To overcome this problem, it can be started through formal education as a place of learning for students. One of the main tools that support the course of formal education is textbooks. In English language learning, the value of character education can be taught through lesson plans, learning media, and learning materials such as textbooks (Utami et al., 2021). Given the importance of textbooks in the learning process, the government, writers, and educators should pay attention to the representation of mutual cooperation values in all subjects, including ELT textbooks. One example from researchers is the study by Mandala and Pujiati (2020) who investigated how the values of mutual cooperation in the PPK program of the 2013 Curriculum are represented through textual materials in ELT textbooks. They found that most of the texts analyzed showed an imbalance in the representation of the value of mutual cooperation, where tolerance dominated among others.
The Chairperson Drs. Bambang Suharjito, M.Ed. The Secretary Ika Fitriani, S.Pd., M.Pd.
Keywords: Analysis; Mutual Cooperation; ELT Textbook